The Relationship Between Subjective Well Being and Grit in High School Athlete Students: Hubungan Antara Kesejahteraan Subjektif dengan Grit pada Siswa Atlet di Sekolah Menengah Atas - Maulana, Syukron Luthfi; Widyastuti, Widyastuti (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the relationship between the subjective well being variable and the grit variable in athletes at SMA Negeri Sport East Java. This study uses a quantitative method with a correlational approach, which involves 210 students in grades X, XI, XII as many as 210 students. This data collection technique uses a psychological scale, namely the subjective well being scale (r = 0.842 ) with a grit scale (r = 0.706 ). The data analysis technique in this study uses product moment analysis with the acquisition of a correlation coefficient of 0.009 with a significance value of 0.901 > 0/05, meaning that there is no relationship between the subjective well being variable and the grit variable in athletes at SMA Negeri Sport East Java. A total of 37% of respondents are in the categorization of moderate subjective well being, and as many as 43% of respondents are in the medium categorization.